United States, ships docked at Ketchikan harbor - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1934)
View of ships docked along marina. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3